2016
DOI: 10.1021/acs.est.6b00826
|View full text |Cite
|
Sign up to set email alerts
|

Depressing Antidepressant: Fluoxetine Affects Serotonin Neurons Causing Adverse Reproductive Responses in Daphnia magna

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are widely used antidepressants. As endocrine disruptive contaminants in the environment, SSRIs affect reproduction in aquatic organisms. In the water flea Daphnia magna, SSRIs increase offspring production in a food ration-dependent manner. At limiting food conditions, females exposed to SSRIs produce more but smaller offspring, which is a maladaptive life-history strategy. We asked whether increased serotonin levels in newly identified serotonin-neurons in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 43 publications
4
33
0
2
Order By: Relevance
“…We previously found that individuals of D. magna exposed to SSRI fluoxetine and fluvoxamine mature earlier and produce more but smaller offspring 12 , 13 . Consistently, fluoxetine increases brain serotonin-immunoreactivity levels at low food conditions, bringing them to the maximal levels normally only observed under high food conditions, and enhancing offspring production concomitantly 14 . Sublethal amounts of the neurotoxin 5,7-dihydroxytryptamine, selectively killing serotonergic neurons, markedly decrease serotonin-immunofluorescence and offspring production in fluoxetine-treated animals, supporting that the observed effect on reproductive phenotype is modulated by serotonin levels 14 .…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…We previously found that individuals of D. magna exposed to SSRI fluoxetine and fluvoxamine mature earlier and produce more but smaller offspring 12 , 13 . Consistently, fluoxetine increases brain serotonin-immunoreactivity levels at low food conditions, bringing them to the maximal levels normally only observed under high food conditions, and enhancing offspring production concomitantly 14 . Sublethal amounts of the neurotoxin 5,7-dihydroxytryptamine, selectively killing serotonergic neurons, markedly decrease serotonin-immunofluorescence and offspring production in fluoxetine-treated animals, supporting that the observed effect on reproductive phenotype is modulated by serotonin levels 14 .…”
Section: Introductionmentioning
confidence: 62%
“…Consistently, fluoxetine increases brain serotonin-immunoreactivity levels at low food conditions, bringing them to the maximal levels normally only observed under high food conditions, and enhancing offspring production concomitantly 14 . Sublethal amounts of the neurotoxin 5,7-dihydroxytryptamine, selectively killing serotonergic neurons, markedly decrease serotonin-immunofluorescence and offspring production in fluoxetine-treated animals, supporting that the observed effect on reproductive phenotype is modulated by serotonin levels 14 . Producing small clutches of larger offspring is an adaptive response to food scarcity in natural conditions, since the larger the offspring the more resistant to starvation 15 .…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The mechanisms of action of the SSRI fluoxetine on D. magna are better known than those of the remaining tested chemicals. Fluoxetine enhances brain serotonin activity in Daphnia (Campos et al, 2016), increases development and reproductive rates (Campos et al, 2012) and alters phototaxis behavior. Recent studies using knockout Daphnia individuals lacking serotonin showed that these animals had the opposite phenotype as those exposed to fluoxetine: animals matured latter, reproduced less and were more mobile than wild type animals (Rivetti et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[3,4,5] Endocrine disrupting activities can lead to adverse effects on exposed organisms, but also on their progeny, creating adverse effects on subsequent generations. [6,7] Nowadays, there is undoubtedly an important concern about the long term ecotoxicity assessment of single chemicals and of multi-contaminated matrixes and the scientific community is actively working to create harmonization (OECD guidelines) of multigenerational bioassays on cladocerans (D. magna)…”
Section: Introductionmentioning
confidence: 99%